Warmer and drier ecosystems select for smaller bacterial genomes in global soils. Issue 1 (3rd January 2023) - Liu, Hongwei; Zhang, Haiyang; Powell, Jeff; Delgado‐Baquerizo, Manuel; Wang, Juntao; Singh, Brajesh
Abstract: Bacterial genome size reflects bacterial evolutionary processes and metabolic lifestyles, with implications for microbial community assembly and ecosystem functions. However, to understand the extent of genome‐mediated microbial responses to environmental selections, we require studies that observe genome size distributions along environmental gradients representing different conditions that soil bacteria normally encounter. In this study, we used surface soils collected from 237 sites across the globe and analyzed how environmental conditions (e.g., soil carbon and nutrients, aridity, pH, and temperature) affect soil bacterial occurrences and genome size at the community level using bacterial community profiling. We used a joint species distribution model to quantify the effects of environments on species occurrences and found that aridity was a major regulator of genome size with warmer and drier environments selecting bacteria with smaller genomes. Drought‐induced physiological constraints on bacterial growth (e.g., water scarcity for cell metabolisms) may have led to these correlations. This finding suggests that increasing cover by warmer and drier ecosystems may result in bacterial genome simplifications by a reduction of genome size. Abstract : We used surface soils collected from 237 sites across the globe and analyzed how environmental conditions affect soil bacterial occurrences and genome size. We used a joint species distribution model to quantify the effects of environments on species occurrences and found that aridity was a major regulator of genome size with warmer and drier environments selecting bacteria with smaller genomes. Highlights: A joint species distribution model was used to quantify the environmental effects on occurrences of bacterial species. Warmer and drier environments favored bacteria with smaller genomes. Higher soil fertility (e.g., phosphorous) favored bacteria with smaller genomes.